-46-16x=2(-23-8x)

Simple and best practice solution for -46-16x=2(-23-8x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -46-16x=2(-23-8x) equation:



-46-16x=2(-23-8x)
We move all terms to the left:
-46-16x-(2(-23-8x))=0
We add all the numbers together, and all the variables
-16x-(2(-8x-23))-46=0
We calculate terms in parentheses: -(2(-8x-23)), so:
2(-8x-23)
We multiply parentheses
-16x-46
Back to the equation:
-(-16x-46)
We get rid of parentheses
-16x+16x+46-46=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 2x−4​(x−4​)=−5+4x+9 | | 5m(2m-9)=3m-2 | | 7(3y+2)=-8(3y-2) | | 7a-22=6 | | -27+7h=-6(5h-3) | | 5(c-4)=35 | | L=10+2w | | 3x+33+4x+8=B | | 9y = 3y12 | | 7x+10-0.5x=2(1/8x+15) | | |-6x+3|=|5x+6| | | -25z+10+7z=16z+7 | | 6f-3+9=-22 | | -3x-4.5=1.5-4x | | -5x+6-3(x-1)=-(4x-5)-3x+3 | | |6x-3|=|5x+6| | | 4^(3x-2)=1 | | 5(-3x+4)=21 | | -6x-(13x+10)=10+(6x+1) | | x=8-(6-9x) | | (1/49)^(x+1)=343^x | | 10.5x-8=4.5x+22 | | 3^(1-2x)=343 | | y-28+110=18 | | (0.96)x(0.06=) | | 10x-4=-1;1/2 | | 31-2x=343 | | j+11=-19 | | 32=7+8(n-9) | | 24t+15=100 | | 3/4+r=29/8+2r | | 9(t-2)=4(t-5) |

Equations solver categories